The nexus between state and corporate: China-tencent ‘forced’ collaboration in governing game industry - Nugroho, Bayu Fajar (Universitas Islam Malang, 2024)
Private enterprise and state sometimes considered as two international relation’s actors that contrast in its orientation and objectives. In this paper, writer want to discuss about the nexus between those two actors. In the more specific way, this paper will discuss about the nexus and the forced collaboration between China as a state and Tencent as a private enterprise in governing internet area in China, especially game industry. In Xi Jinping’s era, China enforce new policy and approach in order to strengthen China’s culture value. In making it happen, Xi Jinping gives concern toward game that is considered as digital addiction which can ruin future generation. Chinese Government itself does not have intrument and capability to direclty govern this sector, hence China choose to enforce forced collaboration with Tencent as biggest China’s private enterprise in game industry to govern the game sector in China. In order to obey government’s policy, Tencent made many afforts to govern game sector, such as blocking and censoring games that considered nor in accordances with the regulation, creating game with patriotism and nationalism value toward China, and limiting under age children’s time to play game. This research examining how the collaboration between state and corporation appear in case of China and Tencent in governing game industry. This research conducted using qualitative data collection techniques taken from various secondary data sources.